Revolution in Eastern Europe : - Peter Cipkowski. (Wiley)
"Our changing world series"--Jacket. Analyzes the fall of communism in Eastern Europe, country by country, during 1989 and 1990. Includes photographs, time lines, maps, and cartoons.